Summary of gastroscopy quality indicators applicable in clinical practice - Machaj, Mikołaj; Budzyń, Krzysztof; Błaszczyński, Gustaw; Romańczyk, Tomasz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
Despite advances in medicine, upper gastrointestinal cancers remain a significant global concern. In Poland, regardless of the increase in performed esophagogastroduodenoscopies, the rate of missed cancers is around 6%. This is related to the insufficient quality measures during the performed examinations. Our paper discusses key endoscopy quality indicators that can enhance the detection of precancerous lesions and cancers. We categorized the indicators into three sections: pre-procedural (fasting time, premedication), intra-procedural (sedation, photodocumentation, virtual chromoendoscopy, quality metrics, biopsy sampling) and post-procedural (coordinated care, training). Some of them, such as chromoendoscopy and premedication in the upper segment, have been widely studied and popularized in recent years. For several years, we have had strict protocols on how to take specimens depending on the condition. Most of the assumptions presented can be easily implemented into daily routine practice, which can improve health care. These are successfully, routinely used in Japan and Korea. We believe that a collective improvement in the quality of esophagogastroduodenoscopies performed will increase the detection rates of precancerous lesions and early cancers. However, further research in this area is still needed.